Relationship between head of department leadership style and job satisfaction among academicians in Nigerian public universities - Sakiru, Oladipo Kolapo (2013)
The relationship between head of departments’ leadership styles and job satisfaction among academicians in Nigerian public universities is an issue of growing importance to the higher learning institution in their preparation to accomplish their mission to become a world class university. An effective leadership style, together with a competent workforce seemed to be a decisive importance for a university to be able to compete in quality and to go along with changes. At present, the empirical linkages between the head of department leadership styles and job satisfaction among acedemicians in Nigerian public universities are not fully established by past researchers. Therefore, it is the aim of this study to investigates the relationship between the selected independent variables, leadership styles (transformational,transactional, lasseir-faire) and job satisfaction as the dependent variables, determine the common leadership style that is commonly used by the head of department, determine the significance differences in job satisfaction and each demographic variables, (age, gender and academic qualifications) and finally determined the predictor variable (leadership styles) on job satisfaction. Thesearch design was descriptive correlational study and data were collected employing questionnaires. The study utilized simple random sampling methods to select 217 lecturers with the response rate of 91.7% from the population of Nigerian lecturers studying at three research universities in Malaysia. The findings showed that statistics revealed that the most commonly used leadership styles among the head of department of Nigeria public university is transformational leadership styles, with the highest mean of 3.9032. One Way Anova revealed that there was no significance difference between lecturers job satisfaction and the demographic variables tested in thisstudy (gender, age and educational qualifications). The result obtained from the correlational analyses revealed that there is a significant relationship between leadership styles of the head of department and lecturers job satisfaction in public universities inNigeria. The result of the multiple regression analysis at 0.05 levels of significant showed that transactional leadership style is the most predictors of job satisfaction. It explains 15.7% of the variance in job satisfaction of the lecturers. The present study contributes useful information for educational leaders and researchers in the field of human resource development.